The Impact of the Introduction of Innovative REDS Scale for the Evaluation of Central Tunnelled Catheter (CTC) Exit Site on Infection Prevention in Long-Term Haemodialyzed Patients - Porazko, Tomasz; Stasiak, Edyta; Klinger, Marian (Frontiers in Surgery, 2021)
Central tunneled catheter (CTC)-related infections are a leading cause of a catheter loss, thus being the source of significant morbidity and mortality. The study aims at evaluating the impact of the implementation of the innovative redness, edema, discharge and tenderness, symptoms (REDS) scale (devised by the authors) for the description of the tunnel condition on the frequency of infection in long-term catheter users. The same cohort of the 40 patients was observed for 4 years altogether: 2 years before and 2 years after REDS application. The results, as well as follow-up evaluation of participants, were compared. The 2-year cumulative incidence of the CTC exit site infection (ESI) dropped significantly (log-rank p < 0.001) from 0.89 episode/1,000 catheter days (53.5%, 95% CI [35.9%; 66.2%]) in the period before REDS was used—to 0.26 episode/1,000 catheter days (18.6%, 95% CI [6.1%; 29.4%]) in the time of REDS application. There were also significantly fewer episodes of ESI complicated with catheter-related blood stream infection (CRBSI) requiring the CTC removal (0.6 episode/1,000 catheter days; 18.6%, 95% CI [6.1%; 29.4%] vs. 0.3 episode/1,000 catheter days; 4.7%, 95% CI [0.0; 10.7%]; log-rank p = 0.04, in pre-REDS and REDS time, respectively). The REDS scale appears to be a simple, cost-effective tool reducing the frequency of the tunneled CTC exit site infection and associated bloodstream infections.